The Essentials about Neonatal Severe Acute Respiratory Syndrome Coronavirus 2 Infection and Coronavirus Disease: A Narrative Review - De Luca, Daniele; Vauloup-Fellous, Christelle; Benachi, Alexandra; Masturzo, Bianca; Manzoni, Paolo; Vivanti, Alexandre (American Journal of Perinatology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection can occur in neonates as the virus can be transmitted both horizontally (from the environment) and vertically (during the pregnancy or at the delivery). Compared to the adult outbreak, neonatal infections do not represent a public health problem. Nonetheless, severe and life-threatening cases may rarely occur and both obstetricians and neonatologists should have a good knowledge of perinatal SARS-CoV-2 infection and related consequences. A high suspicion index must be applied and ruling out neonatal SARS-CoV-2 infection must become a part of the routine clinical workout. Moreover, neonates may be affected by the multisystem inflammatory syndrome, due to a dysregulated host response in the absence of any SARS-CoV-2 infection. We performed a narrative review to summarize here the available literature describing the essentials that should be known by every neonatologist and obstetrician, starting from what has been discovered in 2020 and adding what has been learned in the following years. The paper describes the mechanisms of transmission, clinical features, diagnostic tools, and criteria, as well as possible treatment and prevention strategies. The goal is to provide the practical points to be remembered at the bedside while caring for a pregnant woman or a neonate with suspected or proven coronavirus disease 2019 or multisystem inflammatory syndrome.Key Points
Keywords: coronavirus; neonate; pregnancy; treatment; COVID-19